Understanding Financial Interconnectedness. (Policy Papers; Policy Paper ;, 2010)
This paper seeks to advance our understanding of global financial interconnectedness by (i) mapping aspects of the architecture of global finance and (ii) investigating critical fault lines related to interconnectedness along which systemic risks were built up and shocks transmitted in the crisis. It thus takes initial steps toward operationalizing enhanced financial sector and macro-financial surveillance called for by the IMF's Executive Board and by experts such as de Larosiere and others (2009). Getting a better handle on interconnectedness would strengthen the Fund's ability, together with the Financial Stability Board, to track systemic risk concentrations. It would also inform spillover and vulnerability analyses, and sharpen bilateral and multilateral surveillance.